A new specimen of Millerocaulis (Osmundales: Osmundaceae) from the Cerro Negro Formation (Lower Cretaceous), Antarctica Un nuevo especimen de Millerocaulis (Osmundales: Osmundaceae) de la Formación Cerro Negro (Cretácico Inferior), Antártida - Ezequiel Ignacio Vera (Museo Argentino de Ciencias Naturales Bernardino Rivadavia e Instituto Nacional de Investigación de las Ciencias Naturales, 2010)
A new petrified stem of Millerocaulis Erasmus ex Tidwell emend. Vera, collected in the Aptian Cerro Negro Formation outcrops of Livingston Island (Antarctica), is described in detail. This specimen is probably conspecific with Millerocaulis australis (Vera), from the same unit, but it is smaller than the holotype and only known specimen of the latter species. Furthermore, differences between several characteristics of both specimens are observed. A discussion based on biological aspects of this group of plants is given, taking into account the ontogenetic variability. A conservative referral of the new specimen to M. australis is preferred over the proposal of a new morphotaxon for the inclusion of the new materials. Se describe en detalle un nuevo estípite petrificado de Millerocaulis Erasmus ex Tidwell emend. Vera, colectado en afloramientos de edad aptiana de la Formación Cerro Negro en Isla Livingston (Antártida). Este espécimen es probablemente coespecífico con Millerocaulis australis (Vera), procedente de la misma unidad, pero es mas pequeño que el holotipo (y único ejemplar conocido) de dicha especie. Además, existen diferencias entre ambos especímenes. Se brinda una discusión basada en aspectos biológicos de este grupo de plantas, teniendo en cuenta la variación ontogenética. Se opta por referir de manera conservativa el nuevo espécimen a M. australis, antes que proponer un nuevo morfotaxón para la inclusión de los nuevos materiales.